2005
DOI: 10.1021/cm0482838
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Nanoparticles of ε-Fe2O3 from Yttrium Iron Garnet in a Silica Matrix:  An Unusually Hard Magnet with a Morin-Like Transition below 150 K

Abstract: The elusive ε-Fe2O3 has been obtained as nanoparticles by vacuum heat treatment of yttrium iron garnet in a silica matrix at 300 °C followed by annealing at 1000 °C for up to 10 h in air and employing formamide as a gel modifier. Its nuclear structure is temperature independent as observed from the neutron powder diffraction patterns and has been modeled by the published structures on analogous MM‘O3 compounds. It displays complex magnetic properties that are characterized by two transitions:  one at 480 K fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
126
1
11

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(154 citation statements)
references
References 36 publications
8
126
1
11
Order By: Relevance
“…γ-phase has a spinel structure and ferrimagnetic behavior with a Curie temperature (T C ) of 928 K 1,4 . Recently, an enormously large room temperature coercivity about 2 T was reported on ε-Fe 2 O 3 phase [5][6][7] , but the value is not reproducible 8,9 . It has an orthorhombic structure and is ferromagnetic with T C = 480 K 6,10 .…”
mentioning
confidence: 99%
“…γ-phase has a spinel structure and ferrimagnetic behavior with a Curie temperature (T C ) of 928 K 1,4 . Recently, an enormously large room temperature coercivity about 2 T was reported on ε-Fe 2 O 3 phase [5][6][7] , but the value is not reproducible 8,9 . It has an orthorhombic structure and is ferromagnetic with T C = 480 K 6,10 .…”
mentioning
confidence: 99%
“…The field-cooled magnetization curve under 10 Oe external magnetic field showed a TC value of 496 K and a cusp at 131 K (= Tp). The cusp in the magnetization is due to the spin reorientation phenomenon, which is known to occur in this temperature region [11,12]. The magnetization versus external magnetic field curve exhibited an Hc value of 19.1 kOe at 300 K. For the THz-TDS measurement, ε-Al0.06Fe1.94O3 powder sample was pressed into a pelletform.…”
Section: Temperature Dependence Of Zero-field Ferromagnetic Resonancementioning
confidence: 99%
“…Therefore, the observed anomalous temperature dependence of fr in ε-Al0.06Fe1.94O3 was understood by the temperature dependence of Hc. The sigmoid decrease centered at Tp originates from the disappearance of magnetic anisotropy due to the spin reorientation phenomenon [11][12][13].…”
Section: Temperature Dependence Of Zero-field Ferromagnetic Resonancementioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, we firstly succeeded to obtain a single phase of ε-Fe 2 O 3 nanomagnet (Figure 1), and found that ε-Fe 2 O 3 nanomagnet exhibited an extremely large H c value of 20 kOe at room temperature, which is the highest H c value for insulating magnetic materials. [10][11][12][13][14][15][16][17][18][19] In this paper, we report a new millimeter wave absorber composed of ε-Ga x Fe 2-x O 3 (0.10 ≤ x ≤ 0.67) nanomagnets, which shows a natural resonance in the range of 35-147 GHz at room temperature. 20 This is the first example of a magnetic material which shows a natural resonance above 80 GHz.…”
Section: Introductionmentioning
confidence: 99%